Pengaruh Kepemimpinan Islami, Komunikasi dan Lingkungan Kerja Terhadap Kinerja Karyawan Pt. Bank Syariah Indonesia - Hartini, Kustin; Gustama, Dandy Fendra (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2022)
This study analyzes the factors that affect the performance of employees at BSI S.Parman BengkuluBranch Office. These factors include work environment factors, communication factors, and Islamic leadership factors. Research with associative quantitative analysis approach. Data obtained through observation, questionnaires as well as literature study. The population in this study were employees of BSI Bengkulu Branch Office. Saturated sampling technique in this study was used to determine the research sample and data analysis using regression analysis and statistical data processing with the help of SPSS. The results of partial data analysis for the Islamic leadership variable on employee performance obtained a significance value of 0.007 > 0.05. For the communication variable obtained the value of sig. 0.039 < 0.05 and the work environment variable with a value of sig. 0.003 > 0.05. And the significance value partially shows Islamic leadership variables, communication variables and also work environment variables have a positive and significant influence on the performance of BSI Bengkulu Branch Office employees. Leadership is the ability to influence employees in achieving company goals. Good communication and work environment are also important elements that must be considered in improving employee performance.